2021
DOI: 10.3390/ijerph18115900
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nurse Staffing Grades of Korean Hospitals during COVID-19 Pandemic

Abstract: The global COVID-19 pandemic is creating challenges to manage staff ratios in clinical units. Nurse staffing level is an important indicator of the quality of care. This study aimed to identify any changes in the nurse staffing levels in the general wards of hospitals in Korea during the COVID-19 pandemic. The unit of analysis was the hospitals. This longitudinal study observed the quarterly change of the nurse staffing grades in 969 hospitals in 2020. The nurse staffing grades ranged from 1 to 7 according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In England, a mean of 7.97 patients per registered nurse was found in clinics, with at least 4.85 patients and at most 11.06 patients; while in surgical units, a mean of 7.33 patients per registered nurse was found, with at least 4.60 patients and at most 11.34 patients (Griffiths et al, 2016). A study evaluated the threemonth change in nurse staff grades in 969 hospitals in Korea in 2020 and reported that the score varied between 1 and 7, depending on the nurse-to-patient ratio (Park et al, 2021). In the clinics included in this study, there were at least 5 patients per nurse in the morning shift, and this number was similar to that reported in other studies.…”
Section: Discussionsupporting
confidence: 73%
“…In England, a mean of 7.97 patients per registered nurse was found in clinics, with at least 4.85 patients and at most 11.06 patients; while in surgical units, a mean of 7.33 patients per registered nurse was found, with at least 4.60 patients and at most 11.34 patients (Griffiths et al, 2016). A study evaluated the threemonth change in nurse staff grades in 969 hospitals in Korea in 2020 and reported that the score varied between 1 and 7, depending on the nurse-to-patient ratio (Park et al, 2021). In the clinics included in this study, there were at least 5 patients per nurse in the morning shift, and this number was similar to that reported in other studies.…”
Section: Discussionsupporting
confidence: 73%
“…During the Coronavirus Disease (COVID-19) pandemic, the entire healthcare system around the world was suddenly under so much stress, struggling to cope with an increasing number of patients, leading to an increase in nurses' workloads and physical and mental exhaustion from the frontlines. Thus, a tremendous necessity of nurses was urgently needed, sometimes even relocating nurses from general wards to ICUs, https://doi.org/10.3923/tmr.2023.161.178 | Page 162 thereby reducing the nurse staffing level in general wards 18 . In the nursing literature, traditionally four types of nursing care delivery models (NCDM) are identified and used to organize and provide patients' care, mainly in hospital settings 19 .…”
Section: Introductionmentioning
confidence: 99%
“…If the hospital's nurse staffing grade is 1, the hospital will reimburse all inpatient nursing fees and certain extra financial incentives. In the case of hospitals with a nurse staffing grade of 7, reduced inpatient nursing fees will be reimbursed [19].…”
mentioning
confidence: 99%